The Crime Of Elder Abuse According To Criminal Law Law - Youngky Fernando (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
The aim of this research is to analyze the factors causing abuse by biological children against their parents and the judge's considerations regarding the decision in case Decision Number 421/PidSus/2020/PN.Tgn. This research method uses a normative juridical research approach by reviewing statutory regulations, law books and Islamic law books related to the research focus. The research results show that the factors behind the abuse of biological mothers are economic, family, social environment and social jealousy. Based on the considerations of the judge at the Tangerang District Court with Decision Case Number 421/PidSus/2020/PN.Tgn. Regarding criminal cases, we have referred to legislation no. 23 of 2004 concerning the Elimination of Domestic Violence. However, in terms of justice, the punishment given was not fair for the victim who had been treated badly by his own biological child.